Analisis Hubungan Antara Ketimpangan Ekonomi dan Akses Energi Wilayah Perkotaan di Indonesia Tahun 2012–2022 - Tiar Caroline Citra Purba; Irsad Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the relationship between economic inequality and energy access in urban areas in Indonesia during the period 2012–2022. Economic inequality is measured using the Gini Index, while energy access is represented through household electricity consumption as an indicator of urban electrification. Using secondary data from BPS and ESDM, this study employs a correlational quantitative approach. The findings indicate that electricity consumption in urban households has a relationship with the level of economic inequality, although the strength of this relationship varies across regions. This study highlights the importance of equitable access to energy in supporting inclusive urban economic development.